Inovasi Pelayanan E-KTP di Masa Pandemi Covid-19: Studi Kasus Dinas Kependudukan Dan Pencatatan Sipil Kota Surabaya - Mochammad Haidar Fayyadh (Prodi Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
The purpose of this study is to (1) find out and understand how the implementation of the public E-KTP service at the Population and Civil Registry Service during the Covid-19 pandemic, (2) to find out and understand what innovations the Population and Civil Registry Service have made in E-KTP public service during the Covid-19 pandemic. This research study is a study using descriptive qualitative methods in terms of data obtained from the field. In this study, we will examine using the theory proposed by Sianipar (1998) about public service innovation. The results of the study indicate that during the COVID-19 pandemic, the implementation of E-KTP public services at the Surabaya City Dispenduk and Capil was almost all done online. Because during the pandemic, public services cannot be face-to-face which is useful so as not to massively spread the Covid 19 virus. In carrying out services during the pandemic, of course, there are obstacles experienced, due to differences in the service process before the pandemic. Another obstacle is when the blank E-KTP runs out, it takes a long time, and that obstacle has been experienced since the past until now.